2011
DOI: 10.3109/01676830.2011.603458
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuropathy Following Orbital Irradiation for Graves’ Ophthalmopathy: A Case Report and Literature Review

Abstract: Radiation optic neuropathy (RON) is a devastating complication of radiotherapy to the anterior visual pathway resulting in acute, profound and sometimes irreversible visual loss. Cumulative doses of radiation that exceed 50 Gy or radiation fractions of greater than 2 Gy are usually required for RON to develop. Several factors, such as diabetes and pre-existing compression of the optic nerve, are associated with a higher risk for developing RON at lower doses of radiation. We report a case of presumed subacute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The highest daily highest dose (1 gram of methylprednisolone) showed worsening, unchanged, and improved VA in 3 separate patients. 17,35,36 A subgroup analysis of cases treated within 2 weeks of presentation and normal discs on presentation was conducted. Of the 9 patients, only 3 (33.3%) had improved or stable VA ≤1 logMAR.…”
Section: Resultsmentioning
confidence: 99%
“…The highest daily highest dose (1 gram of methylprednisolone) showed worsening, unchanged, and improved VA in 3 separate patients. 17,35,36 A subgroup analysis of cases treated within 2 weeks of presentation and normal discs on presentation was conducted. Of the 9 patients, only 3 (33.3%) had improved or stable VA ≤1 logMAR.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Despite the widespread use of these modalities over decades for TED, the literature is mostly comprised of retrospective studies, Case reports and small case series which now guide practice patterns in the treatment of DON. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 There has only been one prospective, randomized controlled trial (RCT) to compare corticosteroids versus corticosteroids and surgical decompression for DON. 12 In this study, Wakelkamp et al reported similar initial outcomes after medical decompression and surgical decompression, and found that immediate surgical decompression did not result in better visual outcomes nor did it preclude the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 External beam radiation has also been used for decades for the treatment of active TED including patients with DON. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 Radiation therapy, like corticosteroids, dampens the inflammatory cascade in active TED. 35 …”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was detected between the two groups; suggesting that the addition of 24 Gy irradiation to IV prednisolone had no extra therapeutic benefit. In addition, the radiation may have caused radiation optic neuropathy if the cumulative dose of radiation exceeded 50 Gy or if radiation fractions of >2 Gy were used ( 20 ). In a survey, 91% of the responding members of the European Thyroid Association indicated that they would treat an index patient who had active and severe TAO with glucocorticoids, and 71% would immediately start with IV glucocorticoids ( 21 ).…”
Section: Discussionmentioning
confidence: 99%